EDUKASI KEBIASAAN CUCI TANGAN DENGAN PENERAPAN METODE BERNYANYI SEBAGAI UPAYA PENCEGAHAN PENYAKIT MENULAR PADA MURID SD NEGERI TUADALE KABUPATEN KUPANG - Indriati Andolita Tedju Hinga; Apris Adu (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Children are an age group that is susceptible to infectious diseases such as ARI and diarrhea. Application of Clean and Healthy Behavior (PHBS) in children can prevent the spread of disease. One indicator of a healthy life is the habit of washing your hands. The hand is the main medium of transmission of disease because the hands often make direct contact with various objects that are contaminated with germs that cause disease. The aim of community service is to educate the habit of washing hands as an effort to prevent primary transmission of disease. Problem-solving in this activity uses interactive learning media, namely simulations with singing methods and audiovisual based movements. The target of this activity is students of class II (11 people) and teachers (2 people) in SDN Tuadale, Kupang Regency. The results of the implementation of handwashing habit education greatly affect the number of children's participation at each stage of the activity which reaches 100%. Knowledge and skills of children in the practice of washing hands using the singing method increased to 98%. At the end of the activity the children are already adept at practicing the stages of washing hands properly. Based on these results, the school is an effective forum for implementing health programs, because handwashing habits need to be educated early on. The singing method with audiovisual based movement is effective to be recommended in PHBS counseling especially for children.